Dinamika Kosa Kata Bahasa Bali Kuno dalam Bahasa Bali Moder: Perspektif Fonologis - Sulibra, I Ketut Ngurah; Ratna Erawati, Ni Ketut; Duana Sutika, I Nyoman (Humanis, 2024)
This research is motivated by the fact that Modern Balinese is a continuation of Ancient Balinese. Theoretically, various things in language change are very possible, both microlinguistically and macrolinguistically. This research concerns microlinguistic aspects, especially changes in lexical form and meaning. The aim of this research is to describe changes in the lexical form of Old Balinese in Modern Balinese. The theory used is structural theory. This research is descriptive qualitative in nature. To describe data and analysis, there are three stages of the method used, namely providing data, analyzing data, and presenting analysis results. The data collected is classified based on linguistic characteristics and then described and compared with the initial form and the derived form. Data analysis was carried out using descriptive analytical methods and matching methods. Presentation of results is carried out using formal-informal methods. The results of the analysis show that lexical changes from Old Balinese to Modern Balinese can occur phonologically in both form and meaning. The form of change is in the form of complete lexical changes and some are partial changes.